2009
DOI: 10.3171/2008.9.jns08457
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of the variation in angles of the carpal arch after open and endoscopic carpal tunnel release

Abstract: The widening of the postoperative angles of the carpal arch is a phenomenon observed at the proximal and distal levels of the carpal canal, and it can be noted after both open and endoscopically assisted carpal tunnel release. The endoscopic procedure yielded less increase in these angles than the open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Our data agrees with the clinical observation of Flores et al [8] who reported a 6.2° angular change, in the axial plane, between the hook of hamate and the ridge of the trapezium. This is comparable to the summation of the angular rotations about the pronation/supination axis for the H-C, C-Td, and Td-Tm joints.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our data agrees with the clinical observation of Flores et al [8] who reported a 6.2° angular change, in the axial plane, between the hook of hamate and the ridge of the trapezium. This is comparable to the summation of the angular rotations about the pronation/supination axis for the H-C, C-Td, and Td-Tm joints.…”
Section: Discussionsupporting
confidence: 93%
“…Carpal tunnel release leads to a widening of the CAW up to 3 mm [7] and also results in angular rotations of the distal carpal joints [8]. Our data agrees with the clinical observation of Flores et al [8] who reported a 6.2° angular change, in the axial plane, between the hook of hamate and the ridge of the trapezium.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations